Modelling of black carbon statistical distribution and return periods of extreme concentrations. (December 2015) - Maciejewska, Katarzyna; Juda-Rezler, Katarzyna; Reizer, Magdalena; Klejnowski, Krzysztof
Abstract: Eight datasets of 1-h black carbon (BC) concentrations measured in Warsaw agglomeration (Poland), at urban background and sub-urban sites, and in Racibórz, a small town in Upper Silesia district (regional background site) were analyzed to evaluate BC levels, daily profiles and statistical distributions of concentrations in Central-Eastern European region. The observed mean levels ranged from 1483 ng m −3 in suburban site during summer to 3358 ng m −3 in regional background site in winter. Observed diurnal patterns were bimodal in the locations dominated by traffic emissions, but unimodal, with elevated evening peak in individually heated residential area. Three theoretical frequency distributions were applied to fit analyzed datasets separately. The lognormal distribution was the most appropriate to represent the middle-range values, while the high concentrations were satisfactorily predicted by the type I two-parameter exponential distribution which was used to estimate the return periods of extreme concentrations for winter months. Highlights: BC concentrations in Warsaw are higher than in Western European capitals. Regional background BC levels in Upper Silesia district are high, especially during winter. One or two daily peaks are observed depending on the dominating emission source and season. Lognormal distribution presents the best fit to the middle-range BC concentrations. Return periods of extreme BC wintertime concentrations were estimated.